Eccrine Poroma pada Kulit Kepala: Laporan Kasus dan Tinjauan Histopatologis - Ekawaty Suryani Mastari; Bayu Irvia Satria; Fahmi Irsan Nasution (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Poromas are benign neoplasms composed of epithelial cells that show tubular differentiation, which arises from the intraepidermal part of the eccrine of the sweat glands. This lesion can resemble melanoma or non melanoma.1,2 Case description We reported a case of eccrine poroma in a man, Mr. ES, 50 years old, with complaints of a lump in the head of the temporal region of the region. On macroscopic examination, a blackish-brown scalp tissue size 2x1x0.5 was received, the surface was uneven, the consistency was springy. Microscopic examination of squamous epithelial coating with round, oval, monotone, smooth chromatin, eosinophilic cytoplasm appear. In the sub-epithelium, there is a mass of tumors consisting of proliferative eccrine glands, in groups forming islands, with cuboidal coatings, with round, oval, monotonous nuclei, fine chromatin, eosinophilic cytoplasm. The stroma consists of fibrous connective tissue and blood vessels. The sebaceous glands, hair follicles and infiltration of lymphocyte cells appear. Discussion and conclusions: Based on the results of histopathological examination, it can be concluded as eccrine poroma. In this case electrosurgery is performed, removal with the help of a carbon dioxide laser, or excision surgery can be performed.